Situating information literacy in the disciplines. Issue 2 (8th June 2015) - Farrell, Robert; Badke, William
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this article is to consider the current barriers to situating in the disciplines and to offer a possible strategy for so doing. Design/methodology/approach – The paper reviews current challenges facing librarians who seek to situate information literacy in the disciplines and offers and practical model for those wishing to do so. Phenomenographic evidence from disciplinary faculty focus groups is presented in the context of the model put forward. Findings – Disciplinary faculty do not have generic conceptions of information literacy but rather understand information-related behaviors as part of embodied disciplinary practice. Practical implications – Librarians dissatisfied with traditional forms of generic information literacy instruction marketing will find a method by which to place ownership on information literacy in the hands of disciplinary faculty. Originality/value – The article offers a unique analysis of the challenges facing current information literacy specialists and a new approach for integrating information literacy in the disciplines.